Silagem de capim-zuri colhido em diferentes idades e aditivada com melaço em pó - Omar Ali (2021)
The ideal regrowth age of the forage plant and the use of a fermentation-stimulating additive can improve the fermentative characteristics and nutritional value of tropical grass silages. This study aimed to evaluate the effect of regrowth ages and the use of molasses powder on the nutritional characteristics of silages of Panicum maximum (Syn Megathyrsus maximus) cultivar BRS Zuri. A completely randomized design was used, in a 3x3 factorial scheme: three cutting age (65, 80 and 95 days) and three levels of inclusion of powdered molasses (0, 20 and 40 g) of sugarcane, with four replications each. The chemical composition, fermentation parameters, in vitro digestibility (IVD) and in vitro degradation kinetics of the silages were evaluated. Higher DM contents were observed in silages with 95 days of cut, with 40 g of molasses. The 65 days of cutting silages with 40 g of molasses had higher values for IVD of dry matter (DM) (578,52 g) and IVD of neutral detergent fiber (NDF) (475,17 g). Lower pH values (3,93), ammonia nitrogen (N-NH3) (2,13 %), loss of dry matter (DMP) (56,75 g), loss by gases (GP) (10,65 g) and silage density (DENS) (662,24 kg/cm3) were observed in silages with 95 days of cutting with 40 g of molasse. For the in vitro degradation kinetics, a greater volume of gas (9,97 mL/100 g of DM) was observed in the slow fraction of the silages with 95 days of cutting with 40 g of molasses. It is recommendad to cut the zuri grass between 80 and 95 days of regrowth with the addition of 40 g/kg of powdered molasses for the production of silages.